Synthesis And Characterization Of Some New Metal Complexes Of Ethyl Cyano (2-Methyl Carboxylate Phenyl Azo Acetate) - Sarhan, B. M.; Rumez, R. M.; Hassan, H. A. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
Complexes of (Co2+, Ni2+, Cu2+, Zn2+, Cd2+ and Hg2+) with the ligand Ethyl cyano (2methyl carboxylate phenyl azo acetate) (ECA) have been prepared and characterized by FTIR, (UV-Visible), Atomic absorption spectroscopy, Molar conductivity measurements and magnetic moments measurements. The following general formula has been suggested for the prepared complexes [M(ECA)2]Cl2 where M = (Co2+, Ni2+, Cu2+ ,Zn2+, Cd2+, Hg2+) and the geometry is octahedral.